CHLAMYDIAL INFECTION MONITORING WITHIN WILD MAMMALS IN UKRAINE - Ксьонз, I.M.; Зезекало, В.К.; Передера, С.Б.; Щербакова, Н.С.; Передера, Ж.О.; Koнe, M.С.; Рак, T.M.; Кравченко, С.O.; Канівець, Н.С. (World of Medicine and Biology, 2019)
The study was carried out on of rectal epithelial scrap samples from 117 wild mammals of 16 species, namely 39 wild swine (Sus scrofa), 4 roe deer (Capreolus capreolus), 17 red foxes (Vulpes vulpes), 5 wolves (Canis lupus), 2 raccoon dogs (Nyctereutes procyonoides), 1 badger (Meles meles), 1 polecat (Mustela putorius), 2 beavers (Castor fiber), 3 martens (Martes), 2 weasels (Mustela erminea), 2 river otters (Lutra lutra), 3 muskrats (Ondatra zibethicus), 18 hares (Lepus europaeus), 4 bobak marmots (Marmota bobak), 5 squirrels (Sciurus) and 9 mole rats (Talpa europaea) caught or shot during hunting in hunting areas of 14 regions of Ukraine.
Keywords: monitoring; chlamydial infection; wild mammals; PCR; Ukraine